The Cold War: A Very Short Introduction - McMahon, Robert J. (New York Oxford University Press, 2003)
How, when, and why did the Cold War begin? What impact did it have on the United States, the Soviet Union, Europe, and the Third World? Finally, what difference did it make to the history of the second half of the twentieth century? This overview of the Cold War aims to invite debate and encourage investigation.
Includes Index and Illustrations.
Keywords: Cold War (1945-1989)